PRACTICAL USE OF TEACHING MATERIALS IN THE FORM OF COMIC MATH USING REALISTIC MATHEMATICS EDUCATION (RME) APPROACH IN LEARNING IN JUNIOR HIGH SCHOOL STUDENTS - Novferma Novferma; Nizlel Huda; Silfiani Indri (Cakrawala Pedagogik, 2022)
The purpose of this study was to determine the practicality of Teaching Materials in the form of Mathematical Comics using the Realistic Mathematics Education (RME) approach in learning for junior high school students. Comics are reading materials that are generally more in demand than textbooks by children, especially teenagers. Based on its characteristics, comics contain stories in the form of: Images and text are loaded in text balloons and presented in the form of panels. If comics are presented like the application of a realistic mathematical approach, especially in learning mathematics, it is expected to create an interesting learning atmosphere for students. This research is a development research with ADDIE model. The population in this study were all students of class X SMAN 1 Jambi. While the sample is class X-1 as many as 15 students. The instruments in this study were individual tests by teachers and small group tests by students. Based on the analysis of the data, it was found that the results obtained from the teacher's response questionnaire were 89.40% including practical criteria and student assessments in the form of small group tests 92.40% with very practical criteria. Results Based on the assessment, the mathematical comics developed are valid and can be used as additional material.